High Performance Concrete - Pyo, Sukhoon (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The innovations in construction materials that have been made due to the development of different varieties of concrete have led to innovations in structural applications and design. This Special Issue mainly focuses on state-of-the-art research progress in high-performance concrete, including the effect and characteristics of fibers on the properties of high-performance concrete, the CO2 curing efficiency of high-performance cement composites, and the effect of nano materials when used in ultra-high-performance concrete. This Special Issue also contains two comprehensive review articles covering the following topics: the role of supplementary cementitious materials in ultra-high-performance concrete and recent progress in nanomaterials in cement-based materials. Readers working towards conducting research on innovative construction materials will be exposed to findings related to this topic in this Special Issue.